AlCl3/Cyclohexane Mediated Electrophilic Activation of Isothiocyanates: An Efficient Synthesis of Thioamides. Issue 12 (9th August 2016) - Kumar, Kapil; Konar, Debabrata; Goyal, Sandeep; Gangar, Mukesh; Chouhan, Mangilal; Rawal, Ravindra K.; Nair, Vipin A.
Abstract: An efficient protocol was developed for the Friedel Crafts type thioarylation for the synthesis of aromatic/heteroaromaticthioamide derivatives from aryl isothiocyanates and electron rich aromatic/heteroaromatic molecules by employing the Lewis acid AlCl3 and the less hazardous solvent cyclohexane at 70°C. The developed protocol offers advantages over the previous methods such as use of stoichiometric amount of reactants/reagent, less toxic solvent, shorter reaction time and higher yields. Abstract : An efficient protocol was developed for the Friedel‐Crafts thioarylation using aryl isothiocyanates and electron rich aromatics/heteroaromatics employing the Lewis acid and less hazardous solvent cyclohexane. The developed protocol advantages over earlier methods are the use of stoichiometric amount of reactant/reagent, less hazardous solvent, shorter reaction time and higher yields.